High-Precision Isotopic Analysis of Cu and Fe via Multi-Collector Inductively Coupled Plasma-Mass Spectrometry Reveals Lipopolysaccharide-Induced Inflammatory Effects in Blood Plasma and Brain Tissues - Hobin, Kasper; Costas-Rodríguez, Marta; Van Wonterghem, Elien; Vandenbroucke, Roosmarijn E.; Vanhaecke, Frank (Frontiers in Chemistry, 2022)
The concentration and the isotopic composition of the redox-active essential elements Cu and Fe were investigated in blood plasma and specific brain regions (hippocampus, cortex, brain stem and cerebellum) of mice to assess potential alterations associated with neuroinflammation induced by lipopolysaccharide (LPS) administration. Samples were collected from young (16-22 weeks) and aged (44-65 weeks) mice after intraperitoneal injection of the LPS, an endotoxin inducing neuroinflammation, and from age- and sex-matched controls, injected with PBS. Sector-field single-collector inductively coupled plasma-mass spectrometry was relied upon for elemental analysis and multi-collector inductively coupled plasma-mass spectrometry for isotopic analysis. Significant variations were observed for the Cu concentration and for the Cu and Fe isotope ratios in the blood plasma. Concentrations and isotope ratios of Cu and Fe also varied across the brain tissues. An age- and an inflammatory-related effect was found affecting the isotopic compositions of blood plasma Cu and cerebellum Fe, whereas a regional Cu isotopic redistribution was found within the brain tissues. These findings demonstrate that isotopic analysis of essential mineral elements pick up metabolic changes not revealed by element quantification, making the two approaches complementary.